Syngas Production from Updraft Co-Gasification Process Using Compost, Coffee Husk, and Coal as a Raw Materials - Dewajani, Heny; Zamrudy, Windi; Ariani, Ariani; Arianto, Anang; Nur Abror Falah, Muhammad (Universitas Negeri Semarang, 2023)
The coffee husk biomass from plantation products and compost from household waste processing is currently underutilized. Therefore, efforts are needed to enhance the value of compost and coffee husk as raw materials for producing syngas through co-gasification processes. Due to the low calorific values of these materials, it is necessary to add materials with higher calorific values. In this study, low-quality coal was used for this purpose. The research aims to investigate the influence of airflow rate and mass composition of raw materials on the quality of syngas which produced through the updraft co-gasification process. The stages conducted in this study include raw material pretreatment and characterization, gasification process, and syngas analysis. The experimental variables used were the percentage composition of raw materials, consisting of coffee husk and coal, and airflow rates of 10, 15, 20, and 25 liters per minute. The research results indicate that syngas with the highest Lower Heating Value (LHV) was produced from the co-gasification process using raw materials with a composition of 75% coffee husk and 25% coal, along with an airflow rate of 20 liters per minute. The LHV of the syngas was 5045.56 kJ/m3, consisting of 20.28% CO and 6.89% H2.